2019
DOI: 10.1001/jamanetworkopen.2019.6570
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives to Increase Colorectal Cancer Screening Uptake and Decrease Disparities

Abstract: IMPORTANCEColorectal cancer screening rates are suboptimal, particularly among sociodemographically disadvantaged groups.OBJECTIVETo examine whether guaranteed money or probabilistic lottery financial incentives conditional on completion of colorectal cancer screening increase screening uptake, particularly among groups with lower screening rates.DESIGN, SETTING, AND PARTICIPANTSThis parallel, 3-arm randomized clinical trial was conducted from March 13, 2017, through April 12, 2018, at 21 medical centers in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
(65 reference statements)
0
37
1
Order By: Relevance
“…The literature in this area is evolving, as currently available randomized trials have had mixed results. [74][75][76][77] Future research is likely to clarify whether and how financial incentives may augment FIT completion in response to mailed outreach. We did not include a formal key question focused on the cost-effectiveness of patient navigation for abnormal FIT follow-up; however, evidence regarding the costeffectiveness of patient navigation across the cancer continuum for multiple cancers recently has been summarized.…”
Section: Limitationsmentioning
confidence: 99%
“…The literature in this area is evolving, as currently available randomized trials have had mixed results. [74][75][76][77] Future research is likely to clarify whether and how financial incentives may augment FIT completion in response to mailed outreach. We did not include a formal key question focused on the cost-effectiveness of patient navigation for abnormal FIT follow-up; however, evidence regarding the costeffectiveness of patient navigation across the cancer continuum for multiple cancers recently has been summarized.…”
Section: Limitationsmentioning
confidence: 99%
“…8,14,15 In contrast to these findings, the quantitative analysis of our trial found that both a guaranteed incentive of $10 and probabilistic incentive of a 1 in 10 chance of winning $50 were effective at increasing FIT testing, but not colonoscopy. 16 Our qualitative findings help explain the difference found in this trial, in that participants often had strong feelings about colonoscopy based on their own or their loved ones’ prior experiences. Thus, they stated that small financial incentives would not compel them to complete a colonoscopy.…”
Section: Resultsmentioning
confidence: 63%
“…These qualitative findings provide context to the results from our parent, quantitative study, in which financial incentives were found to significantly increase FIT uptake among individuals who reported making decisions based on how easy they were to do as well as among patients with high opt-out defensive processing (e.g., “if I feel healthy I don’t go the doctor”). 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 A mailed FIT plus a $10 reward for screening completion, or mailed FIT plus entry into a lottery for a 1 in 10 chance of receiving $50 on screening completion achieved a higher proportion of FIT return compared with a mailed FIT alone. 21 However, when colonoscopy adherence was included with FIT, overall CRC screening was not significantly improved with either financial incentive. Another study reported that sending an email with the phone number to schedule a colonoscopy with a $100 incentive to undergo colonoscopy increased screening compared with the email alone, although the absolute increase in screening was less than 5%.…”
Section: Interventions To Increase Crc Screeningmentioning
confidence: 94%